Transforming Engineering Education Globally-The IUCEE Way - Vedula, Krishna (Journal of Engineering Education Transformations, 2012)
During the past four years, a unique program, Indo US Collaboration for Engineering Education (IUCEE) has started to make a significant impact on the quality of engineering education in India. More than 100 US engineering faculty are participating in this effort, which is already showing results in over 100 colleges all over India. This paper summarizes these accomplishments. The 124 Faculty Leadership Institutes which have been conducted, have directly impacted more than 3000 Indian faculty and lakhs of students in their classrooms. After initial financial support from donors and in-kind support from industry, IUCEE is now on its way to becoming financially sustainable with the assistance of a consortium of 45 college, all over India. The recent creation of the IUCEE Virtual Academy for delivering Webinar lectures by world class US faculty, directly to classrooms in India, has ope/led up the possibility of scaling up the program to make an enormous impact on engineering education in India while creating opportunities for unique teaching and research collaborations between Indian and US institutions. This paper analyzes the lessons learnt from the work done so far. Other countries are now showing interest in emulating the IUCEE model.